Umpatan dalam Bahasa Jawa Tondano para Pedagang di Pasar Yosonegoro Limboto Barat: Penelitian - Hikmah Nuratikah; Supriyadi; Asna Ntelu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to describe the form of swear words in Tondano Javanese by traders at Yosonegoro Market, West Limboto, describe the function of swear words in Tondano Javanese by traders at Yosonegoro Market, and describe the meaning of swear words in Tondano Javanese by traders at Yosonegoro Market, West Limboto. The supporting theories used are the theory of swear words by Wijana (2013) to determine the forms of swear words, the theory of swear words by Allan & Burridge (2006) to identify the use of swear words in the daily communication of traders, and the theory of swear words that are relevant in this study, namely literal meaning and connotative meaning. The research method used is a qualitative descriptive method with a sociolinguistic approach and a qualitative descriptive research type. Data collection techniques used in this study are observation techniques, listening techniques without speaking, speaking techniques, note-taking techniques, and sound and image recording techniques. The results of the study show that the forms of swear words found vary, ranging from words, phrases, and clauses. The functions of swear words include expressive functions, aggressive functions, satire functions, and humor/familiarity functions. The meaning of swear words includes two meanings: literal meaning and connotative meaning. The use of swear words is strongly influenced by certain situations.